2022
DOI: 10.1039/d1sc03865f
|View full text |Cite
|
Sign up to set email alerts
|

Cu(i) catalysis for selective condensation/bicycloaromatization of two different arylalkynes: direct and general construction of functionalized C–N axial biaryl compounds

Abstract: Selective condensation/bicycloaromatization of two different arylalkynes is firstly developed under ligand-free copper(i)-catalysis, which allows the direct synthesis of C–N axial biaryl compounds in high yields with excellent selectivity and functional group tolerance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 105 publications
(33 reference statements)
0
8
0
Order By: Relevance
“…[61] The reaction involved Cu(OAc) 2 -promoted intramolecular cyclization followed by further indolylation in hexafluoroisopropanol (HFIP) solvent ( Scheme CuI-mediated assembly of o-alkynylanilines 27 with oacetylaryl alkynes 28 to afford 1,1'-naphthylindoles 29 was demonstrated by Zhou's group. [62] This is an important example of step-economic synthesis of CÀ N axial biaryl compounds via selective condensation/bicycloaromatization of two different arylalkynes (Scheme 10). Notably, the coupled five-six aromatic rings were generated through the selective formation of two C(sp Oxidative cyclization of o-alkynylanilines 30 could be performed via copper catalyzed radical approach to obtain 2hydroxy-2-aryl indol-3-ones 31.…”
Section: Annulations Involving O-alkynylanilinesmentioning
confidence: 99%
“…[61] The reaction involved Cu(OAc) 2 -promoted intramolecular cyclization followed by further indolylation in hexafluoroisopropanol (HFIP) solvent ( Scheme CuI-mediated assembly of o-alkynylanilines 27 with oacetylaryl alkynes 28 to afford 1,1'-naphthylindoles 29 was demonstrated by Zhou's group. [62] This is an important example of step-economic synthesis of CÀ N axial biaryl compounds via selective condensation/bicycloaromatization of two different arylalkynes (Scheme 10). Notably, the coupled five-six aromatic rings were generated through the selective formation of two C(sp Oxidative cyclization of o-alkynylanilines 30 could be performed via copper catalyzed radical approach to obtain 2hydroxy-2-aryl indol-3-ones 31.…”
Section: Annulations Involving O-alkynylanilinesmentioning
confidence: 99%
“…Zhou and co-workers found that the Cu( i )-catalyzed reaction worked efficiently in the presence of Cs 2 CO 3 in HFIP, allowing a direct formation of key intermediate imine Int40-3 by dehydration. 78 This intermediate then undergoes both 6- endo-dig carbocyclization and 5- endo-dig aza-cyclization to C–N axial biaryl compounds.…”
Section: Catalytic 6-endo-dig Carbocyclizationmentioning
confidence: 99%
“…Tang et al documented the formation of N -indolyl or N -benzofuranyl indole scaffolds via Cu-catalyzed tandem cyclization of o -alkynylanilines with cyclohexadienimines or cyclohexadienones, respectively, in the presence of 1,2-DCE (Scheme c) . Recently, Zhou et al proposed a Cu-catalyzed strategy in HFIP for the construction of C–N axial biaryl compounds using o -amino and o -carbonyl aryl alkynes (Scheme d) . In addition to alkynes, 2-alkynylanilines have shown good reactivity with nitriles as well.…”
mentioning
confidence: 99%
“…8 Recently, Zhou et al proposed a Cu-catalyzed strategy in HFIP for the construction of C−N axial biaryl compounds using o-amino and o-carbonyl aryl alkynes (Scheme 1d). 9 In addition to alkynes, 2-alkynylanilines have shown good reactivity with nitriles as well. Wang et al documented a BF 3 •Et 2 O promoted synthesis of 4-amido cinnolines using a diazotization and cyclization sequence of o-alkynylanilines in the presence of t-BuONO (TBN) (Scheme 1e).…”
mentioning
confidence: 99%